Identification, characterization, kinetics, and molecular docking of flavonoid constituents from Archidendron clypearia (Jack.) Nielsen leaves and twigs. Issue 14 (15th July 2016) - Thao, Nguyen Phuong; Luyen, Bui Thi Thuy; Kim, Jang Hoon; Jo, Ah Reum; Dat, Nguyen Tien; Kiem, Phan Van; Minh, Chau Van; Kim, Young Ho
Graphical abstract: Abstract: In our search for natural soluble epoxide hydrolase (sEH) inhibitors from plants, we found that the methanolic extract of the leaves and twigs of Archidendron clypearia (Jack.) Nielsen (Fabaceae) significantly inhibits sEH in vitro. In a phytochemical investigation of the water layer of A. clypearia, we isolated two new chalcones, clypesides A–B (1 –2 ), 13 flavonoid derivatives (3 –15 ) and established their structures based on an extensive 1D and 2D NMR, CD data, and MS analysis. All of the flavonoid derivatives inhibited sEH enzymatic activity in a dose-dependent manner, with IC50 values ranging from 10.0 ± 0.4 to 30.1 ± 2.1 μM. A kinetic analysis of compounds4, 8 –10, 12, 13, and15 revealed that the compounds8 –10 were non-competitive, 4, 13, and15 were mixed-type, and12 was competitive inhibitors. Additionally, molecular docking increased our understanding of their receptor-ligand binding. These results demonstrated that flavonoid derivatives from A. clypearia are potential sEH inhibitors.